The Influence of Product Quality on Positive Word-of-mouth Communication, Case Study at Kedai Wak Edoy Malang - Muhammad Yasir Arafat Pohan (Quantitative Economics and Management Studies, 2022)
Product quality is a very important element in marketing, especially in the aim of generating positive word-of-mouth communication. The number of businesses in the culinary field has resulted in rampant competition, entrepreneurs in the culinary field compete with each other to benefit both local and foreign entrepreneurs because at this time many culinary businesses in Indonesia are owned and run by foreigners. Circumstances like the above are a challenge for local culinary entrepreneurs so they don't lose competitiveness and lose consumers, therefore local entrepreneurs must make new innovations so they don't lose consumers. This research on the effect of product quality on word-of-mouth was conducted to determine whether the quality of products sold at Kedai Wak Edoy Malang can directly move word-of-mouth and whether product quality has an effect on making consumers recommend each other to buy at Kedai Wak Edoy Malang. This study uses a quantitative approach, the data collection technique uses a questionnaire/questionnaire technique, the analytical tool used is multiple linear regression with t test and f test. The case study in this research is that Kedai Wak Edoy Malang can directly move word-of-mouth and whether product quality has an effect. In addition, data collection was carried out on consumers of Kedai Wak Edoy Malang. Where for the taste variable has a t count (4.416) > t table (1.987) and a significant value (0.000) < 0.05. for the Hygienic Product variable has a t count (2.406) > t table (1.987) and a significant value (0.018) < 0.05. for Variation Product variable has t count (2.198) > t table (1.987) and significant value (0.031) < 0.05. for the size variable, it has t count (2.413) > t table (1.987) and significant value (0.018) < 0.05. for the variable Size has t count (2.247) > t table (1.987) and significant value (0.027) < 0.05. The results of the t test also show that the most dominant variable influencing the emergence of positive WOM communication is the taste variable with a regression coefficient (beta) of 0.376.